Considerations for Implementing a Virtual Education Model: A Review of Strategic Areas - Susana Isabel Jiménez-Sánchez; Carlos Vargas-López (Universidad Nacional, Costa Rica, 2011)
In this essay, based on a literature review related to the core areas of a virtual education model, we propose some guidelines for those people interested in implementing virtual or bimodal academic programs in the Universidad Nacional, Costa Rica. We worked on the following seven strategic areas on which the virtual education model should be based: philosophic, academic, teacher, student, technical, legal, financial, geographic, management. For each area, this paper provides: a) a summary of trends in e-learning best practices, b) recommendations from experts for the effective management of virtual or bimodal university programs, c) a brief review of UNA's experiences in this field. Finally, some suggestions are provided for each strategic area that should be considered by the Universidad Nacional focusing on the success and sustainability of virtual and bimodal study programs.